Faktor-Faktor yang Memengaruhi Kompetensi Penyuluh Narkoba dalam Penyuluhan Digital - Rizal, Afib; Fatchiya, Anna; Sadono, Dwi (Jurnal Penyuluhan, 2021)
Utilization of digital media for an extension is a solution the improvement of the competence of Anti-Narcotics extension agents. This study aims to analyze the influence of the individual characteristics of the extension agents, patterns of digital media use, institutional support, and characteristics of innovation on the competence of Anti-Narcotics extension agents. This research was conducted in October 2020 - January 2021 through a census of 170 (98%) functional officers of Anti-Narcotics extension agents throughout Indonesia who have worked for approximately two years. The research instruments were questions, statements (telephone and message), and interviews which were conducted using the digital application Google Form and WhatsApp. Data were processed using Partial Least Square. The results showed that the use of digital media by extension agents consisting of patterns of digital media use, characteristics of innovation, institutional support, and competence of Anti-Narcotics extension agents in the field of information and communication technology were in the Medium category. The competence of Anti-Narcotics extension agents in the use of digital media was in the medium category. This competence is influenced by factors of digital media utilization patterns, innovation characteristics, and institutional support.